Surviving Firms of the Syrian Arab Republic : A Rapid Assessment - Salmon, Kinley; Assaf, Nabila; Francis, David (World Bank, Washington, DC, 2018)
This paper details the results from the first comprehensive survey of private firms across major urban areas in the Syrian Arab Republic -- including Aleppo, Homs, Hama, Latakia, and Damascus -- since the conflict began in 2011. This builds on the World Bank's Enterprise Survey from 2009 and attempts to survey each of the 508 firms from 2009 again. The survey highlights the major challenges facing firms in Syria today, such as access to electricity, fuel, and water. Yet, loss of workers, managers, and supply chain relationships are also notably severe. Rebuilding the social and human capital of Syria may be even more difficult than the bricks and mortar. The paper also identifies the ways firms have been affected in their prices, sales, supply chains, taxation, and costs as well as how they have adapted in financing and employment. These constraints and impacts are also analyzed at the subnational level and across sectors. Firms in Aleppo stand out for their uniquely difficult challenges and responses that are sometimes at odds with the rest of the country. Finally, the paper analyzes firm exit from 2009 to 2017 and finds that higher productivity firms from 2009 were more likely to survive, except in Aleppo where the reverse holds. The paper hypothesizes that productive firms facing the particularly severe destruction in Aleppo may have made a different calculation compared with productive firms elsewhere: to use their capabilities to leave rather than to use their capabilities to weather the storm.